(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The objectives of this study were to determine the richness, abundance, and diversity of bacteria in stray dogs (Canis lupus familiaris) infested by ticks in Comarca Lagunera, northern Mexico, and to establish their pathogenic and or/zoonotic potential. Materials and Methods: Blood samples from 12 dogs were collected, and their deoxyribonucleic acid was extracted. The V3-V4 region of the 16S ribosomal ribunocleic acid gene was amplified by polymerase chain reaction. Next-generation sequencing (NGS) was performed on a MiSeq Illumina platform, and the data were analyzed using quantitative insights into microbial ecology. Results: The operational taxonomic units resulted in 23 phyla, 54 classes, 89 orders, 189 families, 586 genera, and 620 bacterial species; among them, 64 species and/or bacterial genera with pathogenic or zoonotic potential were identified, some of which have been reported in the literature as relevant to public health (Anaplasma phagocytophilum, Brucella spp., Clostridium spp., Corynebacterium affermentants, Cutibacterium spp., Dietzia spp., Ehrlichia canis, Fusobacterium necrophorum, Leptotrichia spp., Mycobacterium spp., Paracoccus spp., and Roseomonas gilardii). Conclusion: This research offers relevant information on the prevalence of tick-borne diseases as well as other potential zoonotic diseases in the blood of stray dogs parasitized by ticks in northern Mexico. New molecular biology and massive NGS techniques may play an important role in the study and documentation of bacterial profiles from animals in close proximity to humans. Adv. Vet. Anim. Res., 11(1): 132-138, March 2024 http://doi.org/10.5455/javar.2024.k757